Eksplorasi Nilai-nilai Pancasila dalam Pendidikan Menengah Pertama di SMPN 40 Surabaya - Adysti, Rachmania Naura; Himawan, Muhammad Guntur; Firdaus, Nadia Dewi (ANWARUL, 2023)
The term hidden curriculum is often referred to as hidden curriculum, which is a goal that is not written in the syllabus, but its application needs to be considered by every teacher to improve the quality of learning. The function of hidden curriculum is to complement and support the formal curriculum. The purpose of this research is to find out and explore the values of Pancasila at SMPN 40 Surabaya. This research was conducted with a qualitative approach using descriptive method. Data collection techniques in the form of observation and interviews, and by using data analysis techniques in the form of data collection and literature selection. Based on the data obtained, the hidden curriculum is instilled through habituation, for example, every morning there is a prayer activity, then singing the Indonesia Raya song, saying Pancasila, and the habit of singing national songs. In addition, the hidden curriculum can be seen in extracurricular activities, namely paskibra. Students are trained on how to march well and correctly, perform the correct ceremony, raise the flag, and read the text of the Pancasila script or the 1945 Constitution honorably. At SMPN 40 Surabaya, students accept very openly, it is proven by students obeying and following. The result is that SMPN 40 Surabaya students memorize national songs, good and correct ceremonial procedures are more able to follow in accordance with regulatory standards. With this research, it will increase the sense of love for the homeland through habituation as an example of the application of hidden curriculum.